Challenges to Solving the Problem of Plastic Waste - Kang, Jingoo (Advances in Social Sciences Research Journal, 2019)
Plastic waste collecting in the Pacific Ocean is a threat to all nations of the Pacific Rim. Environmentalists estimate that an island of plastic in the Pacific is larger than the land area of Texas, and may be better described as a “continent” rather than an island. The problem is a concern for East Asian nations as well as for the United States. Limiting or banning the use of plastics is not practical or feasible because the use of plastic is woven into our daily habits; plastic is inexpensive, and alternatives have their own environmental consequences. Conventional wisdom advocates for recycling, but for a variety of reasons recycling alone is inadequate to address the growing problem. The reality of recycling is that plastic cannot be 100% recovered; a further reality is that current recycling procedures are inefficient. Financial incentives to greatly improve the recovery of plastic waste must be part of the solution. We must explore new technologies that are capable of decomposing plastics into its original petroleum base for use as fuel to power automotive and aviation transportation, and the myriad other products also made from petrochemicals. With advances in the technology of biodegrading plastic, we can replace crude oil that we currently extract from the ground, with material created from plastic waste. These technologies hold the promise to address several environmental, social, and political problems simultaneously.